NYPD Red 4 - Patterson, James 1947-; Karp, Marshall; Ballerini, Edoardo; Snyder, Jay.; Hachette Audio (Firm) (New York, NY : Hachette Audio, 2016)
When a glitzy movie premier is the scene of a shocking murder and high-stakes robbery, NYPD Red gets the call. Traversing the city's highs and lows, from celebrity penthouses to the depths of Manhattan's criminal underworld, Zach and Kylie have to find a cold-blooded killer - before he strikes again.
Keywords: Police -- Fiction -- New York (State); Murder -- Fiction -- Investigation -- New York (State); New York (N.Y.) -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Audiobooks